ChemInform Abstract: Zeolite‐Like Metal—Organic Frameworks (ZMOFs): Design, Synthesis, and Properties. Issue 13 (March 2015) - Eddaoudi, Mohamed; Sava, Dorina F.; Eubank, Jarrod F.; Adil, Karim; Guillerm, Vincent
Abstract Review: 152 refs.